2021
DOI: 10.1039/d0nj03823g
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide as a therapeutic option for COVID-19 treatment: a concise perspective

Abstract: Among several possible therapies applicable for treating COVID-19, nitric oxide therapy has also gained considerable interest. This article describes the same with mechanistic details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 112 publications
1
26
0
Order By: Relevance
“…The SaNOtize treatment is based on nitric oxide, a cell-signaling nanomolecule that is produced naturally by the body, as a first-in-class drug that has proven to be a potential topical antimicrobial agent to treat a wide variety of bacterial, viral and fungal diseases, including COVID-19 [95][96][97][98][99]. The liquid formulation developed by SaNOtize represents US and EU patented Nitric Oxide Releasing Solution (NORS TM ), a self-administered platform designed to deliver NO, that can also be adapted to create NO releasing gels or creams, while controlling the dose of NO gas that is released.…”
Section: Nasal Delivery Of Nitric Oxide (No)mentioning
confidence: 99%
“…The SaNOtize treatment is based on nitric oxide, a cell-signaling nanomolecule that is produced naturally by the body, as a first-in-class drug that has proven to be a potential topical antimicrobial agent to treat a wide variety of bacterial, viral and fungal diseases, including COVID-19 [95][96][97][98][99]. The liquid formulation developed by SaNOtize represents US and EU patented Nitric Oxide Releasing Solution (NORS TM ), a self-administered platform designed to deliver NO, that can also be adapted to create NO releasing gels or creams, while controlling the dose of NO gas that is released.…”
Section: Nasal Delivery Of Nitric Oxide (No)mentioning
confidence: 99%
“…Studies conducted on seeking the mechanistic details of SARS-CoV-2 virulence have confirmed the respective affinity towards the structural and nonstructural proteins (SP and Nsps). For example, the underlined research indicated that (Nsps) possess the ability to impair and affect the host's innate immune response [12][13][14].…”
Section: Covid-19 Pandemic Outbreak and Sars-cov-2 Virulencementioning
confidence: 99%
“…The high surface activity of surfactants allows them to dictate the chemical stability of applied interest [9,10]. Due to the growing motivation towards contemporary COVID-19 related scientific temper [11][12][13][14], this article has been dedicated to finding the applicability of surface chemistry to aid in designing and developing anticovid drugs and efficacious vaccines for all-time defensive against this dreadful pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 epidemic has seriously affected everyone's life and the economies of countries. [1][2][3][4][5][6][7][8] Generally, viruses as infectious pathogens rely on host cells to continue their life cycle. Structurally, they are mainly composed of nucleic acids, structural proteins and lipid membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reducing the health risks and controlling the SARS-CoV-2 virus is of great importance. [2][3][4][5][6][7][8] Most of these problems can be solved through prevention, rapid diagnosis, disinfection and management of the COVID-19 epidemic. Rapid and timely diagnosis of SARS-CoV-2 infection through immunosensors, disinfection by antiviral materials, and the provision of personal protective equipment with reusable and antiviral capabilities can prevent further spread of the virus and improve the environment, life and economies of nations.…”
Section: Introductionmentioning
confidence: 99%